2019
DOI: 10.1021/acsnano.9b01250
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Nucleotide Analogue Facilitates Base-Calling in Quantum-Tunneling-Based DNA Sequencing

Abstract: Quantum-tunneling-based DNA sequencing is a single molecular technology that has great potential for achieving facile and high-throughput DNA sequencing. In principle, the sequence of DNA could be read out by the time trace of the tunnel current that can be changed according to molecular conductance of nucleobases passing through nanosized gap electrodes. However, efficient basecalling of four genetic alphabets has been seriously impeded due to the similarity of molecular conductance among canonical nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…In the previous reports, it is suggested that sample proportional with transmission, is represented as follow equation. [28][29][30][31] (2) Here, ε is the conductive molecular orbital alignment from gold Fermi level, and This inference is consistent with that analysis with current and duration time provides highest accuracy, that is, the single-molecule signal of each homo-oligomer has characteristics of time and current.…”
Section: Analytical Sciencessupporting
confidence: 77%
“…In the previous reports, it is suggested that sample proportional with transmission, is represented as follow equation. [28][29][30][31] (2) Here, ε is the conductive molecular orbital alignment from gold Fermi level, and This inference is consistent with that analysis with current and duration time provides highest accuracy, that is, the single-molecule signal of each homo-oligomer has characteristics of time and current.…”
Section: Analytical Sciencessupporting
confidence: 77%
“…This was done by performing chronoamperometric measurements using~1.1 nm gap at a bias voltage of 50 mV. This gap size was chosen as it is slightly larger than the dimensions of a single nucleotide (<1 nm) 16,35 . Each analyte type produced current transients that corresponded to specific peak conductance (ΔG), with dGMP (240 ± 36 nS) > dAMP (180 ± 33 nS) > dCMP (161 ± 5 nS) > dTMP (120 ± 10 nS) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although efficient interpretation of each signal is essential for high‐throughput analysis, similarities in molecular conductance seriously impede the statistical interpretation of signals obtained within a short time frame. As previous works have shown theoretically and experimentally, the molecular conductance is highly correlated with the HOMO energy level of the nucleobase ( ϵ HOMO ), more specifically, the physical parameter 1/( E F − ϵ HOMO ) 2 , in which E F is the Fermi energy of the electrode. This indicates the intrinsic difficulties in identifying electron‐withdrawing or electronically neutral modifications, including oxidative variants of methyl groups, such as hydroxymethyl, formyl, and carboxyl groups (Figure A), which result only in small differences in 1/( E F − ϵ HOMO ) 2 of the nucleotides (Table S1 in the Supporting Information).…”
Section: Figurementioning
confidence: 94%
“…To measure the molecular conductance of BzIm‐dU relative to canonical nucleotides, we synthesized BzIm‐dU flanked by two abasic mimics (Figure A). Previous work showed that dG was the most conductive of the canonical nucleotides . Therefore, if BzIm‐dU is further conductive compared with dG, BzIm‐dU will be efficiently detectable due to the high conductance profile over all canonical nucleotides and a high signal‐to‐noise ratio.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation